Effectiveness of herbal medicine as an alternative therapy for burning mouth syndrome: a systematic review - Putri, Nadia Tiara; Nuraeny, Nanan (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Burning mouth syndrome (BMS) is characterized by a burning sensation or dysesthesia of the oral mucosa without accompanying abnormal clinical or laboratory findings. Management of BMS is very important to reduce pain, support nutrition and improve patients’ quality of life. Various studies on BMS therapy have been carried out, one of which is by using alternative materials derived from nature known as herbal ingredients. The objective of this systematic review is to review the effectiveness of herbal medicine to reduce pain in BMS patients. Methods: This systematic review was conducted using the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidelines. Article searches were conducted through Pubmed, Scopus, Science Direct, Cochrane, and Springer Link published from 2012 to 2022 with specific keywords. The search for articles was limited to human studies and randomized controlled trial (RCT), papers written in English and availability of full text. The risk assessment of bias uses the Modified Jadad Scale. Results: Seven articles with good eligibility that meet the inclusion criteria were analyzed. The herbal medicine reviewed were capsaicin (two articles), Aloe vera, catuama, capsaicin, virgin olive oil, chamomile and crocin (one article for each herbal medicine). All of the herbal medicine reviewed were proven to reduce pain in BMS patients, but capsaicin and catuama showed significant differences with the comparison group. Minimal side effects were also observed with capsaicin and catuama. Conclusion: Herbal medicinal ingredients have been proven to be effective, useful and safe alternative therapies for BMS patients.